Titanium dioxide -mediated regulation of enzymatic and non-enzymatic antioxidants, pigments, and diosgenin content promotes cold stress tolerance in Trigonella foenum-graecum L. - Mohamad Javad Babaei; Amin Ebrahimi; Parviz Heidari; Elham Azadvari; Shahrokh Gharanjik; Zeinab Chaghakaboodi (Scientific Reports)
Abstract Abiotic stresses, notably cold stress, significantly influence various aspects of plant development and reproduction. Various approaches have been proposed to counteract the adverse impacts of cold stress on plant productivity. The unique properties of nanoparticles contribute to an enhanced tolerance of plants to challenging conditions. This study explores the impact of titanium dioxide nanoparticles (TiO2 NPs) on cold-stress tolerance in fenugreek, as well as genes expression involved in the diosgenin biosynthesis pathway. Varied concentrations of TiO2 NPs (0, 2, 5, and 10 ppm) were sprayed on fenugreek plants subjected to cold stress at 10 °C during 6, 24, and 48 h. Our findings revealed that the utilization of 2 and 5 ppm of TiO2 NPs, positively influenced pigments biosynthesis and enzymatic and non-enzymatic antioxidant activities. It also effectively reduced electrolyte leakage and malondialdehyde content, mitigating the adverse effects of cold stress. The study also highlighted TiO2 NPs’ affirmative impact on defense signaling pathways, including abscisic acid, nitric oxide, and auxin, in fenugreek. Moreover, TiO2 NPs significantly influenced the expression of genes related to diosgenin biosynthesis. Simultaneous exposure to cold stress and TiO2 NPs led to a substantial increase in diosgenin content, with the upregulation of SEP, SQS, CAS, and SSR genes compared to control conditions. This research indicated that TiO2 NPs application could effectively stimulate fenugreek biosynthesis of primary and secondary metabolites, consequently enhancing plant tolerance to cold stress. The study’s outcomes hold promise for potential applications in the metabolic engineering of diosgenin in fenugreek.